Spotlight on Music Collections: Capital City Records: Edmonton Local Music - Doi, Carolyn; Mann, Raquel (CAML Review / Revue de l’ACBM, 2020)
In the inaugural Spotlight on Music Collections column, Carolyn Doi interviews Raquel Mann, Digital Public Spaces Librarian at the Edmonton Public Library. In this interview, Mann speaks about the EPL’s “Capital City Records: Edmonton Local Music” digital public space, as well as “Voices of Amiskwaciy”, a space for sharing and celebrating local Indigenous content, “Edmonton Stories: A Canada 150 Digital Storytelling Project” and “Open Data at EPL”.